2011
DOI: 10.1002/jcb.23204
|View full text |Cite
|
Sign up to set email alerts
|

Complement regulator factor H in multiple sclerosis

Abstract: A recent proteomic study published in this journal demonstrated lower cerebrospinal fluid (CSF) expression of factor H (fH), an important complement regulator, along with two other complement proteins, in active multiple sclerosis (MS) patients. We have previously demonstrated raised serum fH levels in MS and here, an extended analysis, quantifying fH in CSF, demonstrates no change in fH levels in active disease, but significantly raised levels in progressive disease. These findings support our previous work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…The elevated levels of adipsin in our PPMS patients most likely reflect peripheral immune activation and do not associate with ongoing focal CNS changes seen on MRI. Notably, recently the other member of complement pathway, that is, complement factor H, was found to be elevated in sera of patients with progressive MS but not in RRMS or healthy controls [ 39 ]. Together the available data suggest that elevated levels of adipsin in patients with progressive MS reflect ongoing peripheral immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated levels of adipsin in our PPMS patients most likely reflect peripheral immune activation and do not associate with ongoing focal CNS changes seen on MRI. Notably, recently the other member of complement pathway, that is, complement factor H, was found to be elevated in sera of patients with progressive MS but not in RRMS or healthy controls [ 39 ]. Together the available data suggest that elevated levels of adipsin in patients with progressive MS reflect ongoing peripheral immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that Ingram et al recently suggested that elevated complement factor H is a biomarker of multiple sclerosis disease state. 21 …”
Section: Methodsmentioning
confidence: 99%
“…In patients with relapse, a small and transient, but significant, increase in factor H concentration has been detected when compared to controls [28]. In addition, quantifying factor H levels in CSF indicated no change during active disease but significantly raised levels in progressive MS [29]. However, Li et al have found a decrease in the expression of factor H in the CSF of RRMS patients with active disease when compared to controls [23].…”
Section: Introductionmentioning
confidence: 99%